Preparation and electrical properties of (1-x)Ba0.9Sr0.1[Ti0.8(Fe0.5Nb0.5)0.2]O3-xBiZn0.5Ti0.5O3ceramics - Sukum Eitssayeam (2018)
The (1-x)Ba0.9Sr0.1[Ti0.8(Fe1/3Nb2/3)0.2]O3-xBiZn1/2Ti1/2O3solid solution ceramics were synthesized via a solid-state reaction method where x = 0.02, 0.04, 0.06, 0.08 and 0.10. The structural and electrical properties of these ceramics system were investigated as a function of the BZT content by X-ray diffraction (XRD) and dielectric measurement techniques. The XRD analysis demonstrated that with increasing BZT content in (1-x)BSTFN-xBZT, the structural change occurred from the rhombohedral to the tetragonal phase at room temperature. Changes in the dielectric behaviorwere found to depend on the BZT content. Copyright © Taylor &Francis Group, LLC.